2018
DOI: 10.1016/j.econlet.2017.11.012
|View full text |Cite
|
Sign up to set email alerts
|

The development of non-cognitive skills in adolescence

Abstract: We use a unique longitudinal data set to study the development of non-cognitive skills in adolescence. We measure-for the first time-the development over six years of the recently introduced non-cognitive skill "Grit." We also measure the traditional Big Five personality traits. For Grit, we find significant within-person mean-level increases of about .5 standard deviation units for our sample of adolescent students. These increases are comparable with increases in the Big Five, where conscientiousness, agreea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 15 publications
(16 reference statements)
1
20
0
Order By: Relevance
“…Our findings showed that because of the cold and snow, using AST during winter conditions was not easy and it foremost required commitment and grit. Grit is defined as perseverance and passion for long-term goals [43] and it is a characteristic that can change and develop through life in line with life experience [44]. According to Cosgrove et al [45], physical activity is one way of developing grit as children learn to set goals and achieve them by overcoming adversities.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings showed that because of the cold and snow, using AST during winter conditions was not easy and it foremost required commitment and grit. Grit is defined as perseverance and passion for long-term goals [43] and it is a characteristic that can change and develop through life in line with life experience [44]. According to Cosgrove et al [45], physical activity is one way of developing grit as children learn to set goals and achieve them by overcoming adversities.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Hoeschler et al . () finds further evidence that grit and personality traits develop heterogeneously during adolescence, increasing for some and decreasing for others, highlighting a need to better understand development during this period.…”
Section: Skill Developmentmentioning
confidence: 93%
“…There was evidence of weak (or metric) variance, Δχ 2 (26) = 78.81, p < .001; however, differences between model fit indices were miniscule (e.g., ΔCFI = .001) and comparisons of standardized factor loadings suggested that the only differences were that factor loadings were for the most part stronger for seniors than for freshmen. This finding is intuitive given that youth increase in their ability to respond to surveys as they get older (Hoeschler, Balestra, & Backes-Gellner, 2018). For these reasons, weak invariance was accepted, and structural invariance (i.e., whether the structural model is the same across freshmen and seniors) was tested.…”
Section: Multigroup Semsmentioning
confidence: 99%